Schottky performance variation on r-plane and c-plane of GaN micro truncated-pyramid grown by selective area MOCVD. (1st June 2017) - Chen, Jie; Han, Xiaobiao; Huang, Puman; Chen, Weijie; Liang, Jiezhi; Zhong, Changming; Pan, Zhengzhou; Wu, Zhisheng; Liu, Yang; Zhang, Baijun
Abstract: The electric properties of Pt Schottky contacts on semipolar r -plane and polar c -plane of GaN micro truncated-pyramid are compared. The Schottky diodes of the inclined r -plane sample illustrate a relatively inferior rectified performance than that of the top c -plane GaN in term of the lower Schottky barrier heights, larger ideality factor and reverse leakage current. By depositing Pt metal on the dislocation-free area of the top of GaN micro pyramid, the Schottky performance of r -plane GaN can be slightly improved, but still shows much larger reverse leakage current than that of c -plane GaN. It is found that polarization-related surface states and incorporation of donor impurities, rather than dislocation, should mainly contribute to this remarkable electric discrepancy of the planes.